ChemInform Abstract: Broensted Acid Catalyzed Bisindolization of α‐Amido Acetals: Synthesis and Anticancer Activity of Bis(indolyl)ethanamino Derivatives. Issue 8 (February 2015) - Mari, Michele; Tassoni, Aurora; Lucarini, Simone; Fanelli, Mirco; Piersanti, Giovanni; Spadoni, Gilberto
Abstract The condensation of α‐aminoacetals with two equivalents of indoles offers an efficient synthesis of diindolylmethanes.